The Jazz Singer - Raphaelson, Samson, 1896-1983 (Salt Lake City, UT : Project Gutenberg, 2022)
"The Jazz Singer" by Samson Raphaelson is a play that debuted on Broadway in 1925. Based on Raphaelson's short story "The Day of Atonement," it tells the story of Jakie Rabinowitz, a jazz singer who performs in blackface under the name Jack Robin. His father, an Orthodox cantor, disapproves of his career choice. When his father falls seriously ill during Jack's Broadway debut, Jack must choose between his theatrical breakthrough and his family obligations on Yom Kippur. The play inspired the groundbreaking 1927 film adaptation. (This is an automatically generated summary.)
Wikipedia page on this work: https://en.wikipedia.org/wiki/The_Jazz_Singer_(play)
Based on his story, (3z(BThe Day of Atonement,(3y (Bin Everybody$1 (Bs Magazine, January, 1922.s
Release date is 2022-03-08
Ronald Grenier (This file was produced from images generously made available by the Hathi Trust)
Keywords: New York (N.Y.) -- Drama; Jewish singers -- Drama; Fathers and sons -- Drama; Cantors (Judaism) -- Drama; Jewish families -- Drama